MeerKAT observations of novalike cataclysmic variables - Hewitt, Danté Michael (Department of Astronomy, 2021)
I have conducted a systematic survey of eleven nearby novalike cataclysmic variables in the radio band, using the MeerKAT radio interferometer. Radio emission is detected from four out of the eleven systems: IM Eri, RW Sex, V3885 Sgr and V603 Aql. While RW Sex, V3885 Sgr and V603 Aql had been previously detected, this is the first reported radio detection of IM Eri. These observations have doubled the sample of non-magnetic cataclysmic varaibles with sensitive radio data. I observe that at these radio detection limits, a specific optical luminosity & 2.2 × 1018 erg s−1 Hz−1 (corresponding to MV . 6.0) is required to produce a radio detection. I also find that the X-ray and radio luminosities of the detected novalikes are on an extension of the LX ∝ L ∼0.7 R power law originally proposed for non-pulsating neutron star low-mass X-ray binaries. No other correlations are found between the radio emission and emission in other wavebands or any other system parameters for the existing sample of radio-detected novalikes. In-band (0.9–1.7 GHz) radio spectral indices are measured, and are found to be consistent with reports from earlier work. I construct broad spectral energy distributions for this sample from published multi-wavelength data, and use them to place constraints on the mass transfer rates of these eleven systems. Finally, I also present the results of time-resolved optical spectroscopy of two little-studied systems in the sample: V5662 Sgr and LSIV -08 3. I obtain orbital periods for these two systems that are consistent with previous measurements in the literature.